Do projeto freudiano de uma psicanálise para o povo à inserção da psicanálise no campo da atenção psicossocial - Grotti, Nathália Lamounier (2023)
If it is true that psychoanalysis was born and consolidated within the context of private practice, lending its listening ear to an elite public that had access to it, it is fallacious to claim that the discourse of psychoanalysis is restricted and conditioned to the traditional setting. Nowadays, we find psychoanalysts embedded in various public institutions. The fact is that the predominantly served public by these services presents demands that combine important subjective issues with the complexity of socioeconomic urgencies. In this context, the public mental health worker is daily confronted with the challenge of providing effective treatment for both psychological suffering and material deprivation. In this direction, the present research aims to foster a reflection on some impasses raised during the gradual and ongoing process towards the de-elitization and destandardization of analytic practice through its insertion as a social policy of public health. The relevance of this study is justified by recognizing that this transformative process is constantly threatened by internal and external factors within the psychoanalytic field and subject to significant conservative resistance. The issues raised by the reading of Freud's 1918 project on what would become psychoanalysis for the people permeate this work transversally. It starts with a review of the history of the development of psychoanalysis in Brazil, motivated by the observation that the idea persists that it is not suitable for institutional work with impoverished populations or in contexts of social vulnerability. What is the origin of this conception, and what motivates its perpetuation? Subsequently, in order to equip the reader for the proposed debate, the theory of discourses proposed by Lacan is explored, as it enables the displacement of concerns about the rigor of the analytic situation from the nebulous field of practical formalisms, from what is done or not done, to the discursive field. This is the privileged reading key to reflect upon the polyphonic realm of psychosocial care institutions. With the understanding that the discourse of the master founds the institution, the university discourse guides its bureaucracy, the hysteric's discourse questions crystallized knowledge, and the discourse of the psychoanalyst creates space for the subject's speech, a reflection is proposed on the modes of social bonds implicated by each of them, and the notion of subject in Freudian-Lacanian psychoanalysis is explored. Finally, this dissertation delves into the field of Brazilian public mental health. What can be said about the social bonds established between users and workers in these institutions guided by the ideals of Psychiatric Reform? What are the merits of the model achieved, and what are its points of insufficiency? Without overlooking the importance of achievements in the field of rights, a clinical insufficiency has been identified. Given this, what can be the function of analytic discourse in the field of psychosocial care? It is concluded that the psychoanalyst's discourse fulfills its function in the field of public mental health care by giving space to subjects and safeguarding the support for their singularities. In addition to this, the integration of psychoanalysis into the realm of public care contributes to the process of (de)elitization and (de)standardization of the practice, imposing new challenges and thus pushing it forward